Cote d'Ivoire : Technical Assistance Report-Modernizing the Analysis, Monitoring, and Disclosure of Fiscal Risks. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission about modernizing the analysis, monitoring and disclosure of fiscal risks in Cote d'Ivoire. It was found that existing practices for identifying, monitoring and disclosing fiscal risks are still limited and fall below emerging country standards. There is no centralized process, at the level of the economic and financial ministries, no comprehensive identification, quantification and, even less so, monitoring of fiscal risks. Efforts should continue in the direction of proactive management of fiscal risks. Such management would be a determining factor in maintaining the strong economic dynamic of the Ivoirian economy.